Meningkatkan Wawasan Keberagaman Sosial Budaya Siswa Melalui Pembelajaran PKN Berbasis Media Interaktif Berbantuan LKPD Live Worksheets di Sekolah Dasar - Candra Cuga; Nur Alim Hidayat Patilima; Isnanto Isnanto (SAP (Susunan Artikel Pendidikan), 2023)
This research was conducted because it was still found that learning tends to be boring, which has an impact on student motivation and learning outcomes in Civics learning content in elementary schools. The lack of optimal use of innovative learning tools is one of the contributing factors. For this reason, the application of interactive media and LKPD based on live worksheets is the best solution. This research aims to determine the improvement in Civics learning outcomes in the form of insight into students' social and cultural diversity through the application of interactive PowerPoint learning media assisted by LKPD live worksheets. The research subjects were 20 fifth grade students at State Elementary School 59, East City, Gorontalo City. Data was collected using the essay test method. The results of the research show that there is an increase in insight into socio-cultural diversity as a result of civics learning in class V students. This can be seen in student learning results in initial observations with an average score of 69 and learning completeness of 40%. The learning outcomes in cycle I were an average of 72 and learning completeness was 65%. In cycle II the average was 81 and learning completeness was 90%. This research found that the application of innovative learning tools in the form of interactive learning media assisted by LKPD live worksheets can have a direct impact on the content of Civics learning in the form of learning outcomes and has implications for accompanying impacts that can foster student independence, interest and involvement in learning.